FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN IMUNISASI TETANUS TOKSOID PADA IBU HAMIL - rangkuti, nur aliyah; Sari, Juni Permata; Ramadhini, Delfi (Universitas Aufa Royhan, 2020)
One of causes ofmaternal and infant deaths istetanusinfection caused bythe bacterium clostridium tetani as arsult of unsafe/steril labor. Tetanus toxsoid is the best way to protect the mother and baby from the disease tetanus as a result of not sterile or derived from injuries acquired expectant mothers before giving birth. In Padangsidimpuan at 2017 Tetanus Toksoid immunization reached 41%. This research is to know the factors of the giving Tetanus Toksoid immunization on pregnant women in the health Padangmatinggi at 2019. This research is quantitative research using cross sectional design. Sample research are 91 people of pregnant women at the health Padangmatinggi taken in simple random sampling. By using chi square with 90% significance level α = 0.1. The results of analysis is known the majority of respondents knowledgeable less as much as 86.8%. The majority of respondents being negative as much as 53.8%. There is a relationships between knowledge by administering Tetanus Toksoid immunization in the health Labuhan Rasoki at 2019 with p value = 0.000 (< 0.1), there is a relationship attitude by administering Tetanus Toksoid immunization in health Labuhan Rasoki at 2019 with p value = 0.001 (<0.1). It is recommended to health workers to improve health promotion through public awareness about Tetanus immunization Toksoid to pregnant women.